Protothecosis in hematopoietic stem cell transplantation: case report and review of previous cases. Issue 3 (5th May 2014) - Macesic, N.; Fleming, S.; Kidd, S.; Madigan, V.; Chean, R.; Ritchie, D.; Slavin, M.
Abstract Prototheca species are achlorophyllus algae. Prototheca wickerhamii and Prototheca zopfii cause human disease. In immunocompetent individuals, they cause soft tissue infections and olecranon bursitis, but in transplant recipients, these organisms can cause disseminated disease. We report a fatal case of disseminated P. zopfii infection in an hematopoietic stem cell transplant (HSCT) recipient with bloodstream infection and involvement of multiple soft tissue sites. We review all previous cases of protothecosis in HSCT reported in the literature. Protothecosis is uncommon after HSCT, but has a disseminated presentation that is frequently fatal. It is commonly misidentified as a yeast. Tumor necrosis factor‐alpha inhibitors and contamination of central venous catheters may contribute to development of protothecosis. Optimal treatment approaches are yet to be defined. New agents such as miltefosine may be possible future therapies.